Historical overview of penal institutions of imprisonment in the period from the earliest times to 1917 - Ізосімова, К. С. (Problems of legality, 2013)
The article deals with the creation and development of a system of institutions of the penalty of imprisonment to the most famous monuments of the Russian and Ukrainian law.